Over a million students use our free study notes to help them with their homework
Logically work through the problem: 1) Plot all the information that is available so you can visualise the problem better (always encouraged for graphical questions) 2) Understand that the gradient of the...
cos(2x)=cos2(x)-sin2(x)=2cos2(x)-1Therefore:cos(2x)/cos2(x)=(2cos2(x)-1)/cos2(x)=2cos2(x)/cos2(x) - 1/cosAnswered by Hugo F. • Maths tutor5830 Views
In order to differentiate this we need to use the chain rule- first let u = ax + b. Then differentiating, du/dx = a. By substituting into the original expression, we can obtain y = u^n. Differentiating th...
The quotient rule will need to be applied here.let u = sinx and let v = 2x+1du/dx = cosx and dv/dx =2thus using the quotient rule: (vdu/dx- udv/dx)/v^2(2xcosx +cosx - 2sinx)/ (2x+1)^2
There are two ways to solve this problem. The easiest way is graphically, but that requires little explanation and I am not sure how to show graphs on here so I will explain it algebraically.Because both ...
←
261
262
263
264
265
→
Internet Safety
Payment Security
Cyber
Essentials